Routing in the internet - Huitema, Christian (Prentice Hall PTR, 2000)
Nobody knows more about Internet routing than Christian Huitema, former head of the Internet Architecture Board. Now, he's completely updated his classic best-seller on Internet routing to deliver the critical information that networking and software professionals need right now. Routing in the Internet, Second Edition offers unparalleled practical insight for architecting 21st century enterprise networks.